(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the system of primary schools in the South of Ukraine in the first half of the XIX century. The general periods of development of the system are studied; the stuff of teachers and pupils is characterized. The conclusion about low educational standard of population is made; the reasons of such situation are analized.